Aeration efficiency with nappe flow over stepped cascades - Baylar, A.; Bagatur, T.; Emiroglu, M. E. (Ice Publishing, 2007)
Hydraulic structures can increase dissolved oxygen levels by creating turbulent conditions where small air bubbles are carried into the bulk of the flow. Chute aeration is a particular instance of this. A chute is characterised by a steep bed slope associated with torrential flow. This chute flow may be either smooth or stepped. This paper investigates stepped chutes and how they affect the aeration efficiency. It is demonstrated that stepped chutes are very efficient at oxygen transfer because of the strong turbulent mixing associated with substantial air bubble entrainment and that this advantage becomes more pronounced in the nappe flow regime. In a nappe flow regime, the oxygen transfer on each step results from the flow aeration and mixing in the free-falling nappe, at the plunge point and possibly at the downstream hydraulic jump. An empirical correlation predicting aeration efficiency of one individual step for nappe flow regime was developed. A stepped chute design in terms of aeration efficiency can be optimised using this empirical correlation.
Keywords: environment; hydraulics; hydrodynamics; waterways & canals